The Linkage of Employment to Poverty in Central Java at 2010-2017 - Sartika Andari Murti; Robert Kurniawan (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2020)
In 2017, Central Java was the second largest contributor to the GDP in Java but still has poverty and employment problems. In this research, wellbeing can approach with per capita expenditure. Empirically per capita expenditure has spatial relevance. This study aims to determine the relationship between employment indicators and the spending spatially in Central Java. The variables used are expenditure, labor force participation, labor productivity, minimum wage of regency/city, and the average length of the school. The analytical method used to determine the relationship is spatial panel regression with the Spatial Error Model fixed effect. The results obtained are labor force participation, labor productivity, minimum wage of regency/city, and the average length of the school, and spatial error dependencies have a significant positive effect on expenditure. Suggestions proposed are to increase employment through investments, especially in education, and to increase cooperation between regencies/cities in poverty alleviation efforts.JEL Classification: E2, E22, I3, I32, I38, J2, J21, J23.How to Cite:Murti, S. A., & Kurniawan, R. (2020). The Linkage of Employment to Poverty in Central Java. Signifikan: Jurnal Ilmu Ekonomi, 9(2), 195-206. https:// doi.org/10.15408/sjie.v9i2.14466.